Kinerja Pendapatan Asli Daerah; Analisis Efektivitas Dan Kontribusi Pajak Daerah Pada Badan Pendapatan Daerah Kabupaten Kupang - Rupilu, Wilsna; Nggelan, Thereza Julita; Mudamakin, Agnes Kidi; Tanan, Eugenia H P. (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2025)
Abstract This study aims to determine the effectiveness and contribution of regional taxes as a source of Regional Original Revenue (PAD) at the Kupang Regency Regional Revenue Agency (BAPBD). This study employed qualitative methods. The types and sources of data used in the study were primary and secondary data. Data collection techniques employed were interviews and documentation. Data analysis techniques using effectiveness ratios were used to determine the region's ability to realize targets, while contribution ratios were used to determine the contribution of regional taxes as a source of regional original revenue. The results showed that the level of effectiveness of regional taxes in Kupang Regency fell into the less effective category with an average percentage of 84.98%. Meanwhile, the contribution of regional taxes as a source of regional original revenue at the Kupang Regency Regional Revenue Agency averaged 28.90%, a percentage that falls within the moderate category. The regional government is expected to further improve its performance in regional tax collection in Kupang Regency and to further explore the potential of existing taxes. Keywords: Regional Original Revenue, Effectiveness, Regional Taxes